Investigation of the thermodynamic analysis of solar Energy-Based multigeneration plant for sustainable multigeneration. (October 2022) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Highlights: An innovative solar energy-based multigeneration plant is proposed. Thermodynamic and environmental impact assessment is modeled and investigated. Clean and sustainable hydrogen and ammonia generation are examined. To generate power, a transcritical C O 2 -based Rankine cycle system is integrated. Overall energy and exergy efficiencies are 29.04% and 27.43%, respectively. Abstract: Renewable energy-based multigeneration plants are a huge potential to tackle environmental problems and also to the passing of the carbon-free future. The main goal of the present research is to design and examine the combined cycle motivated by solar energy for multigeneration which is power, hydrogen, ammonia, and freshwater generation. The innovative design multigeneration system is made up of a parabolic trough solar collector, a steam Rankine cycle with high and low-pressure turbines, a transcritical Rankine cycle with a carbon-dioxide fluid, a desalination part, a Proton Exchange Membrane electrolysis, and an ammonia reactor. A comprehensive thermodynamic analysis, environmental impact assessment, and exergo-environmental analysis are addressed to determine the performance and carbon dioxide emission reduction of the overall plant. Furthermore, in this planned research, a thorough parametric evaluation is performed to define how the variation of some significant parameters (e.g., ambient temperature, solar radiation, and collector outlet temperature) has an impact on the cycle's efficiency and useful outputs. The findings of the research analysis indicated that the total net power and hydrogen production capacities are 1654 kW and 0.0025 k g s - 1 . The irreversibility rate is determined as 7047 kW and the parabolic trough solar collector has the uppermost rate among the components. Furthermore, energetic and exergetic performances of the modeled cycle are computed as 29.04% and 27.43%, respectively. Finally, freshwater and ammonia production rates are determined as 1.182 k g s - 1 and 0.004842 k g s - 1, respectively.